Exploring indigenous knowledge and practices of the Gurage community on the biosystematics and utilization of Enset landraces for bone fracture and regeneration: the case of Gurage Zone, central Ethiopia region - Negassa, Temesgen; Meressa, Asfaw; Abdissa, Negera; Degu, Sileshi; Addis, Getachew; Debebe, Eyob; Abdisa, Negessa; W/kidan, Samuel; Belitibo, Dereilo Bekere; Ashenef, Sintayehu; Shanko, Werku; Zuber, Zeynu; et al. (Frontiers in Pharmacology, 2025)
BackgroundEnset (Ensete ventricosum) is a crucial perennial crop in Ethiopia for both food and medicine. The indigenous knowledge and practices of the use and biosystematics of the different Enset landraces are deeply rooted in the community. Enset corms, traditionally used for bone fracture treatment, are rich in phosphorus, potassium, zinc, and calcium supporting bone healing and mineralization. Thus, the study aims to explore the traditional knowledge and practices of the Gurage community regarding Enset folklore biosystematics and the utilization of Enset in bone healing.MethodsThe study utilized semi-structured interviews, focus group discussions, key informant interviews, and field observations to document traditional medicinal uses, cultivation practices, and indigenous biosystematics of Enset in four selected districts or Woredas (Cheha, Ezhe, Enor, and Gumer) of Gurage Zone, Central Ethiopia from 603 respondents. Descriptive statistics were employed for data presentation.ResultsA total of 37 Enset landraces were identified across the study Woredas. Landraces were identified primarily based on leaf and pseudostem color (62%) and size (24.7%). The majority of respondents (57.7%) were knowledgeable about 6–10 Enset landraces, while 21% identified 11–15 varieties. Four landraces Astara (31.3%), Kibinar (22.9%), Dere (22.4%), and Guarye (20.1%)were most commonly used for healing fractured and broken bones. Corms are the major parts of Enset used for healing fractured bones and setting broken bones by mixing them with yogurt, milk, or meat. Enset also serves as livestock fodder (42.3%) and for making household materials (23.3%), with 91.4% cultivated in home gardens. Disease susceptibility, insects, and wild animals were identified as major challenges for Enset production.ConclusionIndigenous knowledge has played a significant role in identifying, classifying, and cultivating Enset landraces. Astara, Kibinar, Dere, and Guarye are the most frequently used Enset landraces for healing fractured and broken bones. Further experimental studies to validate the ethnopharmacological uses of Enset for bone healing are highly recommended.